Psychodrama Techniques To Improve Academic Self-Efficacy In Madrasah Aliyah Students - Hara Permana; Suwarjo Suwarjo (AL-ISHLAH: Jurnal Pendidikan, 2022)
There are several symptoms experienced by students who have low academic self-efficacy, namely quickly giving up when working on difficult exam questions, only understanding some subject matter which they think is easy and not sure if their test scores pass in subjects they do not master. The purpose of this study was to determine the effectiveness of group counseling approach to rational emotive behavior therapy with psychodrama techniques to improve academic self-efficacy in class XI MA Madania Bantul Yogyakarta students. This study uses quantitative research methods using experimental types, this experimental research design uses a quasi-experimental research pattern with a nonequivalent control group design. The design of this study consisted of two sample groups selected by purposive sampling technique, namely the experimental group and the control group, each group consisting of 10 students. The data collection technique used is the Likert scale with the aim of measuring students' academic self-efficacy. The result of this research using independent t test is that the t-count value is greater than the t-table value (23.526 1.734). Based on the results of this test, there is a significant difference in values between the experimental and control groups. So it can be concluded that the hypothesis Ho is rejected and Ha is accepted. This means that psychodrama techniques are effective for increasing academic self-efficacy in class XI students of Madrasah Aliyah.Madania Bantul Yogyakarta.